6 REALITIES OF A NOVICE TEACHER - Paz Ceron, Ana Maria; Portilla Sánchez, Mario Alexander (Revista Huellas, 2017)
This article will discuss the experience of novice teachers in the period of teaching practicum, those contexts we faced and from which we learned, the reality of the practicum as teachers as a part of our professional preparation, and the lessons that all this process gave us and helped us grow as foreign language teachers.